Optimalisasi Peran, Tugas dan Fungsi DPRD Mewujudkan GERBANG RAJA (Gerakan Pembangunan Rakyat Sejahtera) di Kabupaten Kutai Kartanegara - Husni Thamrin; Sitti Aisyah; Gunawan Hasibuan (Collegium Studiosum Journal, 2018)
The supervisory function is the most important thing in the creation of good governance, because it will narrow the space for disgraceful acts, the frequency of disgraceful government actions often occurs in free government, while free government is identical to the implementation of regional autonomy, where the granting of authority and discretion is given to the regions to manage and utilize regional resources optimally for the welfare of the people. In an era of democracy and decentralization like this, it provides space and a bigger role for DPRDs to become partners of the government in the process of democratic governance.